Hashimoto’s thyroiditis reduces central lymph node metastasis risk in papillary thyroid microcarcinoma: an integrated meta-analysis - Zhong, Linkun; Xie, Changlian; Gan, Xiaoxiong; Miao, Jianhang; Wu, Yaming; Yang, Yunyun; Liu, Chizhuai; Li, Yutong (Frontiers in Endocrinology, 2025)
BackgroundHashimoto’s thyroiditis (HT) is the most common comorbidity in patients with papillary thyroid microcarcinoma (PTMC). The necessity of prophylactic central lymph node dissection (CLND) in clinically node-negative (cN0) PTMC cases remains a topic of debate. This study evaluates the risk of cervical lymph node metastasis (LNM) in PTMC patients with concurrent HT.ObjectivesThis study aims to evaluate the risk of central lymph node metastasis (CLNM) in patients with PTMC concurrent with HT. By synthesizing existing literature and conducting a case–control analysis, we seek to enhance individualized risk assessment and inform surgical decision-making for PTMC patients.MethodsWe conducted a search for studies published before 1 June 2025 that assessed the risk of CLNM in PTMC concurrent with HT on PubMed, Embase, and Web of Science. A total of 17 studies involving 11,873 cases were included in this meta-analysis. Additionally, we performed a case–control study through a retrospective analysis of 303 consecutive PTMC patients who underwent surgery between 2017 and 2024.ResultsThe meta-analysis indicated that HT was present in 3,175 of the 11,873 PTMC cases (26.7%). The rate of positive CLNM was significantly lower in the HT group (32.6%) compared to the non-HT group (38.4%), with an odds ratio of 0.75. The false-negative rate was as low as 27.5% when combining ultrasonography (US) and fine-needle aspiration biopsy (FNAB) to evaluate CLN status. Funnel plots showed no significant publication bias. In the retrospective analysis, the CLN examination rate in the HT group was significantly higher than in the non-HT group, yet the incidence of CLNM was lower in the HT group. ROC curve analysis indicated that the TPOAb cutoff point for CLNM was 17.9, with sensitivity and specificity values of 53% and 68%, respectively.ConclusionHT may reduce the risk of CLNM in patients with PTMC, suggesting a protective role. Predictive, preventive, and reliable preoperative evaluations using ultrasound and FNAB enhance the assessment of lymph node status, with TPOAb serving as an important marker. These insights support the development of personalized strategies for early intervention and improved patient management in PTMC.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD420251174681.